Transcriptome analysis provides insight into venom evolution in a seed‐parasitic wasp, Megastigmus spermotrophus. Issue 5 (10th June 2016) - Paulson, A. R.; Le, C. H.; Dickson, J. C.; Ehlting, J.; von Aderkas, P.; Perlman, S. J.
Abstract: One of the most striking host range transitions is the evolution of plant parasitism from animal parasitism. Parasitoid wasps that have secondarily evolved to attack plants (ie gall wasps and seed‐feeders) demonstrate intimate associations with their hosts, yet the mechanism of plant–host manipulation is currently not known. There is, however, emerging evidence suggesting that ovipositional secretions play a role in plant manipulation. To investigate whether parasites have modified pre‐existing adaptations to facilitate dramatic host shifts we aimed to characterize the expression of venom proteins in a plant parasite using a collection of parasitoid venom sequences as a guide. The transcriptome of a seed‐feeding wasp, Megastigmus spermotrophus, was assembled de novo and three putative venoms were found to be highly expressed in adult females. One of these putative venoms, aspartylglucosaminidase, has been previously identified as a major venom component in two distantly related parasitoid wasps ( Asobara tabida and Leptopilina heterotoma ) and may have originated via gene duplication within the Hymenoptera. Our study shows that M. spermotrophus, a specialized plant parasite, expresses putative venom transcripts that share homology to venoms identified in Nasonia vitripennis (both superfamily Chalcidoidea), which suggests that M. spermotrophus may have co‐opted pre‐existing machinery to develop as a plant parasite.